PO212 Prevalence of vitamin d deficiency in a complex neurological rehabilitation unit: a pilot study. (1st December 2017) - Samra, Kiran; Maryam, Zahra; Swayne, Orlando; Farrell, Rachel
Abstract : Vitamin D is essential for bone strength, cell growth and immune function. Sources include sunlight and diet. Deficiency causes fatigue, bone pain and weakness. Recognised in Multiple Sclerosis and spinal cord injury, little data exists in brain injury, stroke and patients in complex neurorehabilitation units. Aim: To investigate frequency of VitD deficiency in a cross-sectional cohort on the neurorehabilitation unit, Queen Square. Methods: Baseline demographics, neurological diagnosis, duration of hospitalisation, diet and vitamin D levels were recorded. VitD was considered normal >50 nmol/L, insufficient 25–50 nmol/L, and severely deficient ≤24 nmol/L. Results: 35 subjects tested, mean age 47 [24–72 years]. Ethnicities; Caucasian=17, Asian=7, Afro-Caribbean=9, Mixed=1. Diagnoses included stroke, inflammatory conditions, infection and trauma. Mean time from neurologic injury to date of test was 139 days [5 – 774]. Most ate a normal diet, 1 took supplements (excluded). Mean VitD was 42 mmol/L [<7–99 mmol/L]. 11 (31.4%) subjects were insufficient and 11 (31.4%) were severely deficient. Conclusions: Prevalence of VitD deficiency was 62%. Testing and supplementation is cheap: test costs 70 p, supplementation costs £8 – £12. A simple test, treatment alleviates symptoms and may reduce fractures in fall prone patients.